Performance and meat quality of Nellore bulls fed crude glycerin combined with soybean oil - Fiorentini, G. [UNESP]; Messana, J. D. [UNESP]; José Neto, A. [UNESP]; Sgobi, E. G. [UNESP]; Castagnino, P. S. [UNESP]; Berchielli, T. T. [UNESP] (Elsevier, 2018)
The objective of this experiment was to determine the effect of crude glycerin combined with soybean oil on the performance and fatty acid composition of the longissimus muscle in Nellore bulls. Twenty-eight Nellore young bulls, each with an initial body weight (BW) of 408 ± 29 kg (age 20 ± 2 months), were used in a completely randomized design over a period of 84 days in a 2 × 2 factorial arrangement. The treatments were diets with crude glycerin at 100 g/kg DM (CG+) or without crude glycerin (CG−); diet with inclusion of soybean oil at 60 g/kg DM (Oil+) or without soybean oil inclusion (Oil−). All diets were composed of corn silage (400 g/kg DM), used as the only source of roughage, and concentrate (600 g/kg DM). The intake of the dry matter (g/kg of body weight), neutral detergent fiber (aNDF) and crude protein decreased with soybean oil inclusion, independent of crude glycerin addition. The aNDF digestibility decreased in diets with soybean oil and without crude glycerin. The DM and organic matter (OM) were most digestible in diets that added crude glycerin but excluded soybean oil. Animals fed soybean oil without crude glycerin exhibited higher intake of linoleic acids, total unsaturated fatty acids (UFA), and total polyunsaturated fatty acids (PUFA) than those fed other diets. There were no effects of oil or crude glycerin feeding on final body weight, average daily gain (ADG), hot carcass weight, subcutaneous fat thickness, or loin eye area (P > 0.05). Animals fed soybean oil incorporate into the muscle 40% more conjugated linoleic acids (CLA) and 32% more linoleic acids compared to other diets. The addition of crude glycerin decreased the elongase index (P = 0.04) in the longissimus muscle. The combination of crude glycerin and soybean oil did not effectively increase performance or unsaturated fatty acid deposition in meat. However, the addition of soybean oil at 60 g/kg DM optimized feed efficiency and did not alter ADG.
Keywords: Beef cattle; Fatty acid; Intake; Lipid profile